2018
DOI: 10.1038/s41590-017-0042-6
|View full text |Cite
|
Sign up to set email alerts
|

Selective autophagy of the adaptor TRIF regulates innate inflammatory signaling

Abstract: Defective autophagy is linked to diseases such as rheumatoid arthritis, lupus and inflammatory bowel disease (IBD). However, the mechanisms by which autophagy limits inflammation remain poorly understood. Here we found that loss of the autophagy-related gene Atg16l1 promoted accumulation of the adaptor TRIF and downstream signaling in macrophages. Multiplex proteomic profiling identified SQSTM1 and Tax1BP1 as selective autophagy-related receptors that mediated the turnover of TRIF. Knockdown of Tax1bp1 increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
118
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(123 citation statements)
references
References 61 publications
5
118
0
Order By: Relevance
“…While our study combined with previous studies implicates a set of genes regulating degradative autophagy in protection against shock, the full extent to which autophagy genes perform functions solely through degradative autophagy is not completely understood. Consistent with a degradative role for autophagy in protecting against endotoxin responses, a role for Atg16l1 in preventing Tax1BP1 accumulation and type I IFN responses in myeloid cells was recently demonstrated (72). Since Atg7 and Atg16l1 both contribute to the E3-like conjugation cascade to generate lipidated LC3 during autophagosome biogenesis, an LC3 conjugation-specific role of these genes in controlling responses of myeloid cells to endotoxin cannot be excluded.…”
Section: Immunology and Inflammationmentioning
confidence: 94%
See 1 more Smart Citation
“…While our study combined with previous studies implicates a set of genes regulating degradative autophagy in protection against shock, the full extent to which autophagy genes perform functions solely through degradative autophagy is not completely understood. Consistent with a degradative role for autophagy in protecting against endotoxin responses, a role for Atg16l1 in preventing Tax1BP1 accumulation and type I IFN responses in myeloid cells was recently demonstrated (72). Since Atg7 and Atg16l1 both contribute to the E3-like conjugation cascade to generate lipidated LC3 during autophagosome biogenesis, an LC3 conjugation-specific role of these genes in controlling responses of myeloid cells to endotoxin cannot be excluded.…”
Section: Immunology and Inflammationmentioning
confidence: 94%
“…Previous studies have demonstrated a protective role for genes regulating multiple steps of the autophagy pathway in different tissues of mice challenged with lipopolysaccharide (LPS)/endotoxin, including Atg7 in liver and kidney (66)(67)(68) and Becn1 and Rubicon in heart (69,70). A protective role for Atg7 and Atg16l1 in the myeloid compartment during endotoxin shock has also been demonstrated (71,72). Mortality from LPS in mice is mediated in part by TNF (73,74), although a specific role for TNF in systemic hyperresponsiveness to LPS in autophagy-deficient mice remains unclear.…”
Section: Immunology and Inflammationmentioning
confidence: 95%
“…Previous studies suggested that autophagy is activated during early phase of sepsis, in which increased expressions of autophagy‐related protein is found to be elevated in injured‐organs (ie, lung, liver and kidney) . Studies attempting to pinpoint autophagy modulation have a protective quality against multiple organs injuries in animal sepsis model, attributed to the prevention of apoptosis, maintenance of the pro‐ and anti‐inflammatory balance, and preservation of mitochondrial integrity . Deficiencies in autophagy gene, such as LC3 and Beclin‐1, result in an exaggerated inflammatory response with the development of organs injury and an increase in death .…”
Section: Sting Signaling and Autophagymentioning
confidence: 99%
“…IRGM interacted strongly with p62, mildly with TAX1BP1, and no interaction was observed with Optineurin, NDP52, and NBR1 ( Supplementary Figure 4F and 4G). Several of the key PRR's (including cGAS and RIG-I) and immune proteins (including STING and TRIF) are shown to be degraded by p62-mediated autophagy (Chen et al, 2016;Liu et al, 2016;Prabakaran et al, 2018;Samie et al, 2018;Xian et al, 2019). From our IRGM-p62 interaction data and the literature, we envisaged that p62 could be the key adaptor protein employed by IRGM for selective autophagic degradation of nucleic acid sensor proteins.…”
Section: Irgm Mediates P62-dependent Autophagic Degradation Of Nucleimentioning
confidence: 67%